أثـر الثقافة التنظيمية على إدارة التغيير التنظيمي دراسة تطبيقية على شركة الإسمنت الليبية المساهمة بمدينة بنغازي (Economic studies journal, 2022)
The study aimed to identify the effect of organizational culture on organizational change management in Libyan Cement Company in Benghazi (Libya) from the employees' point of view. and for achieving the objectives of the study, a case study method was followed. and the primary data were collected for the purposes of this study by using a questionnaire developed by the two researchers based on some previous studies, and the study was conducted on a sample of the employees of the mentioned company, consisting of (168) employee, they were chosen by a simple random method. After conducting the appropriate statistical analysis, the study concluded that the general level of organizational culture among the employees of the company under study was high. It also showed that the general level of organizational change management was high too. The study also showed a statistically significant effect of organizational culture on the organizational change management at a level of significance (1%). It also found a significant effect of each dimension of organizational culture (values, beliefs, norms, and expectations) on organizational change management.
Keywords: Organizational Culture; Organizational Change Management; Libyan Cement Company; Benghazi / Libya